SPIRITUAL URGENCY OF RELIGIOUS AND EXPENSES OF EVIDENCE IN COMBATING CORRUPTION IN INDONESIA - Sulistyowati Sulistyowati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In 1950 - an A Psychologist Erich Fromm says about the most basic things, which should grasp man in her life. In his formulation, that humans have a life orientation that focuses on attaining human qualities (being oriented). Life should not be obsessed just want to reach the attributes of life, such as job title, wealth, or position in the social strata (having oriented). The sudden rise to the surface of the case - a case of corruption involving officials of Law Enforcement and Public Officials, giving an indication that the authority and power, provide opportunities for corruption. The eradication of corruption, must be done comprehensively, because corruption is an extraordinary crime. Eradication of corruption should start from the stage of the prevention / preventive measures, namely the one with the religious spiritual practice. As for the law enforcement phase / repressive measures, that the burden of proof in the trial in court, should be borne by the defendant, and no longer charged to the prosecutor. Prosecutors just enough to make the accusation that the defendant committed the crime of corruption, and it is the defendant who must prove that the defendant is not guilty of corruption .It is called the burden of proof is reversed. Reversal system of the burden of proof, is one way, which can contribute to reduce the number of perpetrators of corruption. During this time, prosecutors had to fight to prove the charges. While the defendant has the right to prove that the property is acquired not from corruption. Because it is only a right and not an obligation, then the defendant can not conduct verification or proof. Therefore, it is necessary juridical changes in the procedural law of evidence for corruption, namely that the burden of proof should and must be done by the defendant, no longer by the Attorney. Based on the description above, there are two (2) issues to be discussed are: 1) How do I make an effort - preventive efforts in the prevention of corruption in Indonesia? and 2) Is the burden of proof reversed, will be able to contribute in reducing the number of perpetrators of corruption in Indonesia?. By discussing the two (2) to these problems, are expected to provide a way out, in efforts to prevent and eradicate corruption in Indonesia, making Indonesia free of corruption is expected by 2020. Keywords: power, corruption, religious spiritual, the burden of proof.